Targeted Next-Generation Sequencing in the Diagnosis of Facial Dysostoses - Bukowska-Olech, Ewelina; Materna-Kiryluk, Anna; Walczak-Sztulpa, Joanna; Popiel, Delfina; Badura-Stronka, Magdalena; Koczyk, Grzegorz; Dawidziuk, Adam; Jamsheer, Aleksander (Frontiers in Genetics, 2020)
Background: Defects in the development of the first and second pharyngeal arches and their derivatives result in abnormal formation of the craniofacial complex, consequently giving rise to facial dysostoses (FDs). FDs represent a group of rare and highly heterogeneous disease entities that encompass mandibulofacial dysostoses with normal extremities and acrofacial dysostoses with limb anomalies in addition to craniofacial defects. Methods: We examined eleven families with variable clinical symptoms of FDs, in most of which only one member was affected. We applied two custom gene panels – first comprising 37 genes related to the genetic disorders of craniofacial development such as FDs (On-Demand AmpliSeq ThermoFisher Scientific gene panel with 2 primer pools) and second composed of 61 genes and 11 single nucleotide variants (SNVs) known to be involved in the development of craniofacial malformations (SureSelect Agilent Technologies). Targeted next-generation sequencing (NGS) was performed using the Ion Torrent S5 platform. To confirm the presence of each detected variant, we have analyzed a genomic region of interest using Sanger sequencing. Results: In this paper, we summarized the results of custom targeted gene panel sequencing in the cohort of sixteen patients from eleven consecutive families affected by distinct forms of facial dysostoses. We have found three novel pathogenic variants in the TCOF1 gene – c.2145_2148dupAAAG p.(Ser717Lysfs*42), c.4370delA p.(Lys1457Argfs*118), c.83G>C p.(Arg28Pro) causing Treacher Collins syndrome type 1, two novel missense variants in the EFTUD2 gene – c.491A>G p.(Asp164Gly) and c.779T>A p.(Ile260Asn) in two female patients affected by acrofacial dysostosis Guion-Almeida type, one previously reported – c.403C>T p.Arg135Cys, as well as one novel missense variant – c.128C>T p.(Pro43Leu) in the DHODH gene in the male patient with Miller syndrome and finally one known pathogenic variant c.574G>T p.(Glu192*) in the SF3B4 gene in the patient with Nager syndrome. Conclusions: Our study confirms the efficiency and clinical utility of the targeted gene panel sequencing and shows that this strategy is suitable and efficient in the molecular screening of variable forms of facial dysostoses.